Analysis of Transformer Loading Profile at 11/0.4 kV Distribution Voltage Network at Hospital Melaka - Azri, Maaspaliza Binti; Othman, Mohd Azlan; Aziz, Nur Hakimah; Badrul Hisham, Nurizzati Hidayatullah; Othman, Md Nazri (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2022)
On distribution site, to offer customers with comfort in service, the dependability, stability, and residual lifetime of the transformer is important part to consider. The factors that affect the lifetime duration of a transformer are the ambient temperature, transformer oil temperature, and pattern of the consumed load. This paper discusses the load current demand profile of the transformers in three substations, Substation 1-3 (SS1-SS3) at Hospital Melaka. The load current demand profile is measured and recorded using Power Logger Fluke 175. The data logger is installed at main switch board feeder 1 and feeder 2 between 10 to 15 days. The normal loading and short time overloading (due to the contingency when the power supply is breakdown) of the transformers are analyzed in this paper. The finding shows that in normal loading conditions, each substation's transformer is loaded between 30% and 60% of its capacity, and its lifespan is anticipated to be more than ten years. Meanwhile, the short-time overloading of step-up distribution transformer at SS2 (TG1 and TG2) can be improved by raising the transformer size to 1600 kVA and 2000 kVA. This could prevent the transformer loading swing over its full capacity in accordance with the IEC 60076-7 guidelines.